Răspuns :
3×{ 10 + 2 × [ 40 - 2 × ( 28 - 3 × 5 )]} -7x = 51
3×{ 10 + 2 × [ 40 - 2 × ( 28-15 )]} -7x = 51
3× [ 10 + 2 × ( 40 - 2× 13 ) ] -7x = 51
3×[10 + 2 × ( 40 - 26 )] -7x = 51
3×( 10 + 2 × 14 ) -7x = 51
3×( 10 + 28 ) -7x = 51
3× 38 -7x = 51
114 -7x = 51
7x = 114-51
7x = 63
x = 63 : 7
x = 9
3×{ 10 + 2 × [ 40 - 2 × ( 28-15 )]} -7x = 51
3× [ 10 + 2 × ( 40 - 2× 13 ) ] -7x = 51
3×[10 + 2 × ( 40 - 26 )] -7x = 51
3×( 10 + 2 × 14 ) -7x = 51
3×( 10 + 28 ) -7x = 51
3× 38 -7x = 51
114 -7x = 51
7x = 114-51
7x = 63
x = 63 : 7
x = 9
ai rezolvarea afișată mai jos:
..................................................................................
sper că te-am ajutat
Redeyes2
..................................................................................
sper că te-am ajutat
Redeyes2